2021
DOI: 10.33633/jpeb.v6i2.4826
|View full text |Cite
|
Sign up to set email alerts
|

How does Unified Theory of Acceptance and Use of Technology (UTAUT) Work on Adopting Financial Technology (FinTech) by MSMEs?

Abstract: Micro Small and Medium Enterprises (MSMEs) have a very significant role in the economy, can even be said to be the backbone of the economy. However, MSMEs are precisely the sector hardest hit by the Covid-19 pandemic. Digitalization creates new opportunities for MSMEs in the pandemic. FinTech, one of the implementations of digitalization should be pursued to be used by MSMEs. Using path analysis processed using Partial Least Square (PLS), this research aims to identify how Unified Theory of Acceptance and Use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
2
2
2
Order By: Relevance
“…However, the effect of EE on intentions to adopt digitalization in SME was statistically insignificant. This finding is in sharp contrast with extant studies (Razak et al, 2017;Wismantoro and Susilowati, 2021).…”
Section: Multi-group Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the effect of EE on intentions to adopt digitalization in SME was statistically insignificant. This finding is in sharp contrast with extant studies (Razak et al, 2017;Wismantoro and Susilowati, 2021).…”
Section: Multi-group Analysiscontrasting
confidence: 99%
“…Again, a manager who perceives a new technology as easier to adopt for his company is more likely to make a positive decision to adopt it and engender the intention to use it. According to various academicians, SME managers will strengthen their intentions to adopt a digital system to the extent that it does not represent a Extending UTAUT with competitive pressure considerable effort (Wismantoro and Susilowati, 2021). This is consistent with findings in the studies conducted by Saad e and Bahli (2005) and Razak et al (2017), which summarize that SME owners often attach great importance to the ease of use of digital tools for their enterprise activities.…”
Section: Effort Expectancysupporting
confidence: 80%
See 1 more Smart Citation
“…The MSMEs business development could be in the form of sales volume, business marketing coverage, it was more sustainable. The transaction online technology supported to do so (Wismantoro & Susilowati, 2021). The findings of this study confirmed the research by Hassan and Rahmawati et al, which found that behavioral fintech has a positive and significant impact on MSME business development.…”
Section: Table 6 Specific Indirect Effectssupporting
confidence: 88%
“…Fintech, one of the implementations of digitalization, is used by MSMEs. The fintech context is the interaction between users and applications that has a significant positive impact on fintech usage intentions (Wismantoro & Susilowati, 2021).…”
Section: Introductionmentioning
confidence: 99%